2014
DOI: 10.1182/blood-2014-01-549741
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous heparin-induced thrombocytopenia syndrome: 2 new cases and a proposal for defining this disorder

Abstract: Key Points Two well-documented cases of a HIT-mimicking disorder without proximate heparin exposure (spontaneous HIT syndrome) are reported. The definition of spontaneous HIT syndrome should include strong serum-induced platelet activation at 0 IU/mL heparin (inhibited at 100 IU/mL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
146
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 23 publications
5
146
1
5
Order By: Relevance
“…A report by Rauova et al 17 that concentrations of PF4 found to be optimal for activation of platelets by HIT antibodies can be achieved "in the immediate environ of activated platelets" (unpublished observations) and by their demonstration that injection of KKO alone causes moderate thrombocytopenia in Fc g RIIa transgenic mice expressing low-range levels of PF4 and severe thrombocytopenia in animals expressing high or mid-range levels of human PF4 17 suggest our findings may be directly relevant to HIT pathogenesis. A subset of HIT antibodies that recognizes PF4 on the platelet surface in the absence of heparin and activates platelets when it binds to this target could account for heparin-independent serotonin release seen with some HIT antibodies 15,37 and the significantly increased thrombotic risk that persists for several weeks to HPA-1a is a serum sample containing antibody to platelet-specific antigen HPA-1a. NC, pooled normal serum.…”
Section: Discussionmentioning
confidence: 99%
“…A report by Rauova et al 17 that concentrations of PF4 found to be optimal for activation of platelets by HIT antibodies can be achieved "in the immediate environ of activated platelets" (unpublished observations) and by their demonstration that injection of KKO alone causes moderate thrombocytopenia in Fc g RIIa transgenic mice expressing low-range levels of PF4 and severe thrombocytopenia in animals expressing high or mid-range levels of human PF4 17 suggest our findings may be directly relevant to HIT pathogenesis. A subset of HIT antibodies that recognizes PF4 on the platelet surface in the absence of heparin and activates platelets when it binds to this target could account for heparin-independent serotonin release seen with some HIT antibodies 15,37 and the significantly increased thrombotic risk that persists for several weeks to HPA-1a is a serum sample containing antibody to platelet-specific antigen HPA-1a. NC, pooled normal serum.…”
Section: Discussionmentioning
confidence: 99%
“…A typical serological feature of "autoimmune HIT" antibodies, is that they bind to platelet factor 4 (PF4) and induce platelet activation even in the absence of heparin [6].…”
Section: Solving Clinical Problems In Blood Diseasesmentioning
confidence: 99%
“…Therefore, long-lasting HIT without dependent on heparin is often called "autoimmune HIT." The term "autoimmune HIT" is also used for the very rare cases where HIT appears without any exposure to heparin [6]. In these patients the …”
mentioning
confidence: 99%
“…Indeed, antibody pathogenicity in the absence of heparin is one of the key features of the pathological anti-PF4/heparin antibodies that have been identified in the sera of patients with so-called spontaneous HIT syndrome. 5 Perhaps these studies also help absolve fondaparinux as being an independent trigger of HIT in the setting of TKA, because the surgery itself could be mainly responsible for triggering the HIT immune response. Conflict-of-interest disclosure: T.E.W.…”
mentioning
confidence: 99%
“…Spontaneous HIT syndrome is a prothrombotic thrombocytopenic disorder with serologic features of HIT (detectability of anti-PF4/heparin antibodies with strong platelet-activating properties) but which occurs despite lack of preceding exposure to heparin. 5 Interestingly, a large proportion of cases of spontaneous HIT syndrome have been reported in patients after orthopedic surgery, especially total knee arthroplasty (TKA). 6 Another mystery relates to how HIT might occur in patients who receive anticoagulation with fondaparinux, 7 the pentasaccharide anticoagulant modeled after the antithrombinbinding region of heparin, but which shows negligible cross-reactivity (enhancement of platelet-activating properties) with HIT antibodies.…”
mentioning
confidence: 99%